Brain cell swelling during hypocapnia increases with hyperglycemia or ketosis. Issue 7 (20th January 2014) - Glaser, Nicole; Bundros, Angeliki; Anderson, Steve; Tancredi, Daniel; Lo, Weei; Orgain, Myra; O'Donnell, Martha
<x xml:space="preserve">Abstract</x> Background Severe hypocapnia reduces cerebral blood flow (CBF) and is known to be a risk factor for diabetic ketoacidosis (DKA)‐related cerebral edema and cerebral injury in children. Reductions in CBF resulting from hypocapnia alone, however, would not be expected to cause substantial cerebral injury. We hypothesized that either hyperglycemia or ketosis might alter the effects of hypocapnia on CBF and/or cerebral edema associated with CBF reduction. Methods We induced hypocapnia (pCO2 20 ± 3 mmHg) via mechanical ventilation in three groups of juvenile rats: 25 controls, 22 hyperglycemic rats (serum glucose 451 ± 78 mg/dL), and 15 ketotic rats (β‐hydroxy butyrate 3.0 ± 1.0 mmol/L). We used magnetic resonance imaging to measure CBF and apparent diffusion coefficient (ADC) values in these groups and in 17 ventilated rats with normal pCO2 (40 ± 3 mmHg). In a subset (n = 35), after 2 h of hypocapnia, pCO2 levels were normalized (40 ± 3 mmHg) and ADC and CBF measurements were repeated. Results Declines in CBF with hypocapnia occurred in all groups. Normalization of pCO2 after hypocapnia resulted in hyperemia in the striatum. These effects were not substantially altered by hyperglycemia or ketosis. Declines in ADC (suggesting brain cell swelling) during hypocapnia, however, were greater during both hyperglycemia and ketosis. Conclusions We conclude that brain cell swelling associated with hypocapnia is increased by both hyperglycemia and ketosis, suggesting that these metabolic conditions may make the brain more vulnerable to injury during hypocapnia.